The Role of Higher Education in Developing an Entrepreneurial Spirit Among Students - Ika Apia Septira; Fitria Sari Ayu; Ratna Sari (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Higher education institutions play an important role in creating an entrepreneurial spirit in students, as one step toward overcoming numerous problems and encouraging students to become people who can create business chances in the future. The purpose of this research is to look at how universities might help students acquire an entrepreneurial spirit. This study employs a qualitative approach, stressing literature analysis as a data source. Using basic data sources such as literature, publications were found, filtered for relevance, then inductively evaluated to extract and synthesize data. The validity was confirmed through meticulous documentation and triangulation. According to the findings of the study, universities play a significant role in the establishment of an entrepreneurial spirit among students by offering entrepreneurship programs that aim to improve the formation of this spirit.